Pengembangan Media Pembelajaran Menggunakan Smart App Creator Berbasis Android Pada Mata Pelajaran TIK di SMPN 12 Cilegon - Reza Habiburrahman; Basrowi Basrowi; Kurniati Rahmadani (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2023)
This research includes research and development that produces valid and practical Android-based ICT learning media for students at SMPN 12 Cilegon. This learning media development model refers to the 3-D development model (Tri D-Model), which consists of 4 stages, namely: define, design, and develop. This research was conducted at SMPN 12 Cilegon with 21 students and one ICT subject teacher as subjects. As for data collection techniques using observation sheet instruments and questionnaire responses from students and teachers, The analysis used in this study is a qualitative descriptive analysis used to analyze the validity of the instruments used in the study. Revision of the media so that results are feasible to use. The results of the study show that the media developed after being validated and declared valid, so it is feasible to test them in the field to determine their practicality. During the small group trials with a total of 21 student subjects, it was shown that the Smart Apps Creator learning media was practical. The trial results showed that the Smart Apps Creator learning media were very practical to use and fulfilled the mix.